Legalidade vs legitimidade: representações sobre a democracia no movimento de luta pela terra (assentamento Nova Tangará, Uberlândia, 1999-2005) - Silveira, Cássio Rodrigues da (2008)
The present text results of a research to analyze the representations of the democracy generated in the conflict in the fight for land, occurred in triângulo mineiro , mainly in Uberlândia, between 1999 and 2005. This region is known for its difficult relations between great landowners and field workers, since, at least, the 60s and 70s, more specifically, as a consequence of government policies which resulted in a benefit for those who held large properties and in some harm for the small land owners. The study is basically divided into three chapters. In the first one, there is a more pormenorized analysis of the land in the referred region, emphasizing the phases, which helps to more clearly understand the excludent factor of the land appropriation in the triângulo mineiro region in general, and in Uberlândia, more specifically. Several pieces of research carried out by students of history, economics and geography at ufu were taken into consideration. In the second chapter, through the study of the lawsuit that originated from a farm occupation by members of a movement of land dispute, some representations which are present in the referred region both of members of the movement and landowners can be assimilated. It is important to ratify that the main theoretical apparatus used to forger such representations was historian roger chartier´s book. At last, in the third chapter, based on the same document in a centered way, there was an analysis of the conflict itself, when the parts explictly direct to each other. In a second part of this chapter a debate with some theoreticians was held in order to draw some conclusions, always insufficient and susceptible to responses, concerning the role of social movements, mainly when those make use of acts of dissidency , in the construction of images and the proper consolidation of democracy, while a social experience.